Female reproductive tract pain: targets, challenges, and outcomes - Jobling, Phillip; O'Hara, Kate; Hua, Susan (Frontiers in Pharmacology, 2014)
Pain from the female reproductive tract (FRT) is a significant clinical problem for which there are few effective therapies. The complex neuroanatomy of pelvic organs not only makes diagnosis of pelvic pain disorders difficult but represents a challenge to development of targeted therapies. A number of potential therapeutic targets have been identified on sensory neurons supplying the FRT but our knowledge on the basic neurophysiology of these neurons is limited compared with other viscera. Until this is addressed we can only guess if the new experimental therapies proposed for somatic, gastrointestinal, or bladder pain will translate to the FRT. Once suitable therapeutic targets become clear, the next challenge is drug delivery. The FRT represents a promising system for topical drug delivery that could be tailored to act locally or systemically depending on formulation. Development of these therapies and their delivery systems will need to be done in concert with more robust in vivo and in vitro models of FRT pain.